Concentration Investigating The Impact of Covid-19 On The Operation and Management of a Dance Studio - Amrullah Ibnus Salam (Green Publisher Indonesia, 2022)
The Coronavirus Disease 2019 (Covid-19) entered Indonesia around March 2020. Covid-19 has been impacting in various fields, including the running of different companies. The current study will take IDOLAB dance studio from Indonesia as an example to understand the operation and management practices after the epidemic. By literature analysis and interviewing with the boss and manager from IDOLAB dance studio, several findings are shown as followings. The major impacts of Covid-19 on IDOLAB include not running dance classes, workshops and other activities, losing most students, and the lack of studio rentals. The operation and management changes in IDOLAB are: (1) The learning process during the pandemic was carried out online. (2) Teachers will teach through an app that can also be accessed by the participant. (3) The company has to solve online classes problems: the network is not smooth, students cannot interpret dance movements, trainers have difficulty evaluating student movements, hampering the process of delivering material, and students are less flexible in performing dance moves. (4) More promoting and marketing through social media such as sharing on Instagram, and WhatsApp is needed. (5) When the pandemic conditions are getting controlled, IDOLAB has some face-to-face classes, but with the condition that it follows the 3M progress, namely washing hands, maintaining distance, and wearing masks. Under the unstable epidemic situation, online classes are still necessary. How to improve the quality of online classes, emphasize the importance of exercises to customers, and promote to find mental support through dance during the epidemic could be the direction that IDOLAB dance studio can do in the future.